2013
DOI: 10.1016/j.freeradbiomed.2012.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Seaweed extracts and unsaturated fatty acid constituents from the green alga Ulva lactuca as activators of the cytoprotective Nrf2–ARE pathway

Abstract: Increased amounts of reactive oxygen species (ROS) have been implicated in many pathological conditions, including cancer. The major machinery that the cell employs to neutralize excess ROS is through the activation of the antioxidant-response element (ARE) that controls the activation of many phase II detoxification enzymes. The transcription factor that recognizes the ARE, Nrf2, can be activated by a variety of small molecules, most of which contain an α,β-unsaturated carbonyl system. In the pursuit of chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(73 citation statements)
references
References 62 publications
3
70
0
Order By: Relevance
“…To confirm activation of the Nrf2-ARE system in the present study, we measured the mRNA expression of Nrf2 gene and three antioxidant genes containing ARE at their promoter regions ( Nrf2 , contains two ARE sequences [33]; HO-1 , a well-characterized Nrf2 target gene [34]; NQO1 , reduces quinones to hydroquinones to protect against oxidative stress [35]; GCLC , combines Glu and Cys as the first step in GSH production [36]). Previous studies have been reported that the activation of Nrf2 induced increased expression of Nrf2, HO-1, NQO1 and GCLC [37,38]. Consistent with the results above, our founding showed an increase in mRNA expression of Nrf2 , HO-1 and GCLC during consecutive heat stress which may reversely promote the expression of oxidative-mediated antioxidant genes via activation of Nrf2 transcription factor (Figure 7).…”
Section: Discussionsupporting
confidence: 92%
“…To confirm activation of the Nrf2-ARE system in the present study, we measured the mRNA expression of Nrf2 gene and three antioxidant genes containing ARE at their promoter regions ( Nrf2 , contains two ARE sequences [33]; HO-1 , a well-characterized Nrf2 target gene [34]; NQO1 , reduces quinones to hydroquinones to protect against oxidative stress [35]; GCLC , combines Glu and Cys as the first step in GSH production [36]). Previous studies have been reported that the activation of Nrf2 induced increased expression of Nrf2, HO-1, NQO1 and GCLC [37,38]. Consistent with the results above, our founding showed an increase in mRNA expression of Nrf2 , HO-1 and GCLC during consecutive heat stress which may reversely promote the expression of oxidative-mediated antioxidant genes via activation of Nrf2 transcription factor (Figure 7).…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, n-3 PUFA have been reported as modulators of the activity of nitric oxide synthase (NOS) (Radosinska et al 2011), one of the primary enzymes involved in NO production. MUFA derivatives have also been isolated from Ulva lactuca which act as activators of the cytoprotective Nrf2 -ARE pathway (Wang et al 2013), linked to suppression of inflammatory responses (Chen and Kunsch 2004). Furthermore, the brown alga Eisenia bicyclis (order Laminariales) was evaluated for anti-inflammatory activity via inhibition against LPS-induced NO and other inflammatory mediators in RAW 264.7 cells as in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols and tertiary butylhydroquinone (tBHQ) activate endogenous antioxidant genes and also activate ARE reporter constructs in human IMR-32 neuroblastoma cells (11,(15)(16)(17). IMR-32 cells (ATCC) were grown and maintained in MEM (Life Technologies) containing 10% heat-inactivated FBS (hiFBS; Sigma), 13 nonessential amino acids (MEM NEAA; Life Technologies), 1 mM pyruvate (Hyclone), and 100 U/mL penicillin-streptomycin (Life Technologies).…”
Section: Methodsmentioning
confidence: 99%